Elective nodal irradiation versus involved-field irradiation for stage II–IV cervical esophageal squamous cell carcinoma patients undergoing definitive concurrent chemoradiotherapy: a retrospective propensity study with 8-year survival outcomes - Jianing Wang; Yajing Wu; Wei Zhang; Yujia Chen; Qing Liu; Shaowu Jing; Jiandong Zhang; Fengpeng Wu; Jun Wang; Xueying Qiao (Radiation Oncology, 2023)
Abstract Background Definitive concurrent chemoradiotherapy (dCCRT) is suggested as the standard treatment for cervical esophageal squamous cell carcinoma (CESCC). This retrospective propensity study compared the 8-year survival outcomes and acute treatment toxicities of these patients treated with elective nodal irradiation (ENI) versus involved-field irradiation (IFI). Materials and methods Patients with stage II–IV CESCC treated with dCCRT at the Fourth Hospital of Hebei Medical University between January 1, 2007 and December 31, 2020 were enrolled in the study. All the patients were restaged according to the American Joint Commission 8th edition criteria. The propensity score matching (PSM) was used to minimize the effects of treatment selection bias and potential confounding factors including sex, age, ECOG score, clinical T stage, clinical N stage, clinical TNM stage and radiation dose between the ENI group and IFI group. Survival and the prognostic factors were evaluated. Results The 131 eligible patients underwent ENI (60 patients, 45.8%) or IFI (71 patients, 54.2%). The median follow-up time was 91.1 months (range, 23.8–182.0 months) for all the patients. The median OS, 1-, 3-, 5-, and 8-year OS rates were 44.4 months, 87.8%, 55.1%, 38.3%, and 27.2%, respectively. After PSM, there were 49 patients in each group. The median OS, 1-, 3-, 5-, and 8-year OS rates for ENI and IFI group were 32.0 months, 83.7%, 48.5%, 38.5% and 31.1% versus 45.2 months, 89.8%, 52.5%, 37.5%, 26.1%, respectively (P = 0.966; HR 0.99, 95% CI 0.61–1.61). Similar locoregional control was obtained in both groups. The tendency of leukocytopenia and neutropenia was higher in ENI than in IFI (59.2% vs. 38.8%; P = 0.068 and 30.6% vs. 14.3%; P = 0.089) at the end of dCCRT. Conclusion Cervical esophageal squamous cell carcinoma patients undergoing definitive concurrent chemoradiotherapy has a satisfactory prognosis with organ conservation. The involved-field irradiation might be a better alternative owing to similar overall survival outcomes and local control with less toxicity of myelosuppression.